Addressing the missing linkage in sustainable finance: the 'SDG Finance Taxonomy'. (3rd April 2022) - Nedopil Wang, Christoph; Lund Larsen, Mathias; Wang, Y.
ABSTRACT: Achieving the United Nation's (UN) Sustainable Development Goals (SDGs) is said to require USD 5–7 trillion of investments in areas such as health, education, environmental protection, and infrastructure. While several frameworks exist to mobilize and to some extent report on sustainable finance, stakeholders have no agreement how to identify SDG-aligned projects and report on relevant impact indicators. Targeted at investors and governments to drive sustainable investment in China and across the globe, the UNDP SDG Finance Taxonomy launched in June 2020 provides a unified taxonomy of activities for sustainable finance that incorporates all 17 sustainable development goals (SDGs). In doing so, the taxonomy provides a clear pathway for identifying SDG-aligned projects for financing, reducing transaction costs, and is compatible with existing frameworks.